PERSPEKTIF RAMAH ANAK, PEREMPUAN, KELOMPOK BERKEBUTUHAN KHUSUS DAN LANSIA PADA PELAYANAN TRANSPORTASI PUBLIK DI KOTA BANDARLAMPUNG - Ita Prihantika; Ani Agus Puspawati; Bambang Utoyo Sutiyoso; Fitri Fatharani (Wacana Publik, 2021)
This article describes the perspective of being friendly to children, women, special needs groups and the elderly on public transportation services in Bandar Lampung City. Using a qualitative research approach with interview, observation and documentation data collection techniques, it shows that the technical aspects, social aspects, gender aspects, disability aspects, and environmental aspects that are expected in public transportation services are not fulfilled. The Bandarlampung City Government does not yet have a legal basis that specifically pays attention to groups of children, women, special needs and the elderly.